Measurement of the stress field of a tunnel through its rock EMR. (23rd June 2017) - Qiu, Liming; Wang, Enyuan; Song, Dazhao; Liu, Zhentang; Shen, Rongxi; Lv, Ganggang; Xu, Zhaoyong
Abstract: In order to quantitatively study the relationship between the disturbance stress of coal mine roadways and the electromagnetic radiation (EMR) of rocks, and further evaluate their internal stress distributions, we first examined the characteristics of EMR signals emitted from rock mass under uniaxial compression, analyzed the relationship between the stress inside the rock mass and its emitted EMR intensity, and put forward a new disturbance stress testing method by monitoring the EMR from the rock mass to retrieve its surrounding stress field. Then, we applied the method to monitor EMR intensity from the no.11803 rock roadway of the Nuodong coal mine, China, and inversely retrieved its stress field. Lastly, we analyzed the causes of local stress anomalies in the Nuodong area by testing the EMR intensity of its nearby areas, and we examined the geology of the whole region. The results showed that: (1) in the rock roadway and the surrounding area of the Nuodong coal mine, the disturbance stress was in the range of 4.8 ∼ 9.1 MPa, the angle between the direction of the stress field and the horizontal plane of the roadway was 35 ± 2.5°, the lateral pressure coefficient was 1.30 ∼ 1.57; (2) the Laoguishan and Yulong anticlines in the vicinity of the Nuodong coal mine caused great horizontal tectonic stress in the region, and the existence of the auxiliary roadway and F12 normal fault resulted in the formation of two high stress zones in the no.11803 rock roadway. Overall, monitoring the EMR from rock mass could ascertain the state, direction, size and distribution of disturbance stress in a roadway and further obtain the distribution of the stress field of an underground structure.